The burden of CDI in the United States: a multifactorial challenge - Feuerstadt, Paul; Theriault, Nicolette; Tillotson, Glenn (BMC infectious diseases, 2023)
Clostridioides difficile infection (CDI) affects approximately 500,000 patients annually in the United States, of these around 30,000 will die. CDI carries significant burdens including clinical, social and economic. While healthcare-associated CDI has declined in recent years, community-associated CDI is on the rise. Many patients are also impacted by recurrent C. difficile infections (rCDI); up to 35% of index CDI will recur and of these up to 60% will further recur with multiple recurrences observed. The range of outcomes adversely affected by rCDI is significant and current standard of care does not alter these recurrence rates due to the damaged gut microbiome and subsequent dysbiosis. The clinical landscape of CDI is changing, we discuss the impact of CDI, rCDI, and the wide range of financial, social, and clinical outcomes by which treatments should be evaluated.